MENINGKATKAN HASIL BELAJAR SISWA KELAS III MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE WORD SQUARE DI SD NEGERI XXV WAILITI, SIKKA NUSA TENGGARA TIMUR - ALOYSIA MAURITSIA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study was designed to address the problem of the low learning outcomes of third grade students of XXV State Elementary School Wailitipada Theme I Subtema I about the Characteristics of Living Things. Based on the records and evaluation results of teachers in the previous Academic Year, for some subjects student learning outcomes have decreased. This condition is caused by the new teacher applying the learning model according to the demands of the 2013 curriculum so that not all learning components can be carried out properly. In addition, the teacher still applies conventional teaching patterns by prioritizing lecture methods in the lesson. Students are less involved in learning, so students become passive, lazy, and do not emphasize teamwork / group learning. To overcome these problems teachers are encouraged to show enthusiasm and present learning materials in new forms, so that students do not feel bored or bored. One way to overcome student boredom is by managing an effective and enjoyable learning process by using a learning model that is fun and attracts students to learn with the teacher. Many learning models that can be used by teachers in learning, one of which is Word Square. Based on the results of research on the application of the Word Square type cooperative learning model in Theme 1 Subtheme 1 about the Characteristics of Living Creatures in class III Wailiti XXV State Elementary School that researchers have carried out in several cycles, the conclusions can be drawn as follows: (a) Application of the learning model Word Squared cooperative type in learning belongs to the very good category and is able to trigger maximum student involvement in the learning process so that it can motivate students to improve their learning outcomes; (b) Student learning outcomes experience changes for the better after applying Word Square type cooperative learning models in learning. Student learning outcomes improve because students are very enthusiastic and actively participate in the application of the Word Square type cooperative learning model.